2013
DOI: 10.4321/s0004-05922013000400019
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen balance of barrows (15-30 kg) fed low protein and different digestible isoleucine levels

Abstract: SUMMARYTwenty crossbred castrated barrows, averaging 22.26 ± 1.79 kg of body weight, were used. The animals were individually alloted in metabolic cages, in a randomized blocks design, with five treatments (0.45, 0.52, 0.59, 0.66 and 0.73 % of digestible isoleucine) and four replicates. The diets were based on corn and soybean meal with low crude protein (14.15 %) and different levels of digestible isoleucine. The diets were humidified and supplied twice a day (7 am and 7 pm) to reduce losses and facilitate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A higher catabolism of amino acids, observed only in N in PIC piglets, promoted an effect on TNE since fecal and urine N are used to determine absorbed and retained N. The highest TNE did not change urine N concentration. This could cause lower N intestinal absorption and greater N usage (Castilha et al, 2013). Additionally, when energy intake is lower than maximum N deposition requirement, urine N excretion would increase (Zhao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher catabolism of amino acids, observed only in N in PIC piglets, promoted an effect on TNE since fecal and urine N are used to determine absorbed and retained N. The highest TNE did not change urine N concentration. This could cause lower N intestinal absorption and greater N usage (Castilha et al, 2013). Additionally, when energy intake is lower than maximum N deposition requirement, urine N excretion would increase (Zhao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, studies have shown that it is necessary to adapt diets according to production systems and tropical conditions, considering genetics and environmental and health conditions (Paul et al, 2007;. Thus, evaluating different ingredients and diet formulations to meet the requirements of modern pig genetics (Rostagno et al, 2017), such as formulating low-crude protein diets (Castilha et al, 2013;Toledo et al, 2014;Souza et al, 2023), have shown positive effects mainly in reduced environmental impact, but starter pigs fed low CP-based diets grew more slowly (Ruusunen et al, 2007), and increased feed intake due to lower essential amino acid content in the diet (Schiavon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Dourmad et al [20], the reduction in urinary N elimination results from the decrease in the amount of N absorbed through of the intestine and the increase in the use of N. The lack of effect of protein sources on the crude protein intake can be correlated to the absence of significance for the variable ingested N, considering that both are interconnected [22]. The net protein utilization of 64.62% to 67.22% in the current study were similar to 65.5% and 60.8% obtained by Oliveira et al [23], who worked with growing pigs and concentrations of 12% and 14% of CP in feeds.…”
Section: Resultsmentioning
confidence: 99%